The Influence of Supplier Involvement on Communication, Relationship Longevity and Business Performance in Small, Medium and Micro Enterprises in South Africa - Chinomona, Richard (Journal of Economics and Behavioral Studies, 2015)
Most firms are increasingly realizing the benefits of involving the outside suppliers by considering their manufacturing processes and technological capabilities, especially regarding quality, time to market, configuration, control and cost. Nevertheless, in the context of small to medium enterprises (SMEs), scant attention has been given to the empirical investigation into the influence of supplier involvement on business performance. The purpose of this study was to examine the influence of supplier involvement on business performance and the mediating role of communication and relationship longevity among SMEs in South Africa. Five hypotheses were posited and sample data of 302 were collected from Gauteng Province of South Africa, to empirically test these hypotheses. The results of this study showed that, supplier involvement has influence on communication, relationship longevity and business performance in SMEs context in South Africa. The managerial implications of the findings are discussed and limitations and future research directions are indicated.